Predictors of dopamine agonist resistance in prolactinoma patients - Elle Vermeulen; Jean D’Haens; Tadeusz Stadnik; David Unuane; Kurt Barbe; Vera Van Velthoven; Sven Gläsker (BMC Endocrine Disorders, 2020)
Abstract Background Surgical resection of prolactinomas resistant to dopamine agonists is frequently incomplete due to fibrotic changes of the tumour under pharmacological therapy. In order to identify a subgroup of patients who may benefit from early surgery, we thought to investigate possible predictive factors of pharmacological resistance of prolactinomas to dopamine agonists. Methods We retrospectively analyzed a database of a Belgian tertiary reference center for patients with pituitary tumours from 2014 to 2016. The groups of interest were patients with dopamine agonist responsive and resistant prolactinomas. The possible predictive factors, including MRI findings, endocrinological parameters, response of tumour and patient factors for dopamine agonist resistance were investigated. Results We included 69 patients of whom 52 were women (75,4%) and 17 were men (24,6%). Rate of dopamine agonist resistance was 15.9%. We identified four significant predictors of dopamine agonist resistance: male gender, a large tumour volume, prolonged time to prolactin normalization and presence of a cystic, hemorrhagic and/or necrotic component. In addition, symptoms due to mass effect, high baseline prolactin level and a high contrast capture on MRI are factors that can be taken into consideration. Conclusion We identified predictive factors for pharmacological resistance and developed a scoring system for patient specific prediction of resistance to dopamine agonists. This scoring system may have impact on the timing and decision of surgery in prolactinoma patients after further prospective evaluation.